Intrinsic capacity rather than intervention exposure influences reversal to robustness among prefrail community-dwelling older adults: A non-randomized controlled study of a multidomain exercise and nutrition intervention - Tay, Laura; Tay, Ee-Ling; Mah, Shi Min; Latib, Aisyah; Ng, Yee-Sien (Frontiers in Medicine, 2022)
Background: The differential risk profiles associated with prefrailty may be attributable to underlying intrinsic capacity (IC). Objectives: We examine (i) effect of a multi-domain physical exercise and nutrition intervention on pre-frailty reversal in community-dwelling older adults at one-year, and (ii) whether IC contributes to pre-frailty reversal. Methods: Prefrail participants in this non-randomized study were invited to attend a 4-month exercise and nutritional intervention following a frailty screen in the community. Prefrailty was operationalized as (i) FRAIL score 1-2 or (ii) 0 positive response on FRAIL but with weak grip strength or slow gait speed based on the Asian Working Group for Sarcopenia cut-offs. Participants who fulfilled operational criteria for prefrailty but declined enrolment in the intervention programme served as the control group. All participants completed baseline IC assessment: locomotion (Short Physical Performance Battery, 6-minute walk test), vitality (nutritional status, muscle mass), sensory (self-reported hearing and vision), cognition (self-reported memory, age- and education adjusted cognitive performance), psychological (Geriatric Depression Scale-15, self-reported anxiety/ depression). Reversal of prefrailty was defined as achieving a FRAIL score of 0, with unimpaired grip strength and gait speed at 1-year follow-up. Results: Of 81 participants (70.0+6.6 years, 79.0% female), 52 participants (64.2%) were enrolled in the multi-domain intervention, and 29 participants (35.8%) who declined intervention constituted the control group. There was no difference in age, gender and baseline composite IC between groups. Reversal to robustness at 1-year was similar between groups (30.8% vs 44.8%, p=0.206). Reduced prevalence of depression was observed among participants in the intervention group at 1-year relative to baseline (7.8% vs 23.1%, p=0.022). In multiple logistic regression, intervention had no effect on prefrailty reversal, while higher composite IC exhibited reduced likelihood of remaining prefrail at 1-year (OR=0.67, 95% CI 0.45-1.00, p=0.049). Conclusion: Focusing only on the locomotion and vitality domains through a combined exercise and nutritional intervention may not adequately address component domain losses to optimize prefrailty reversal. Future studies should examine whether an IC-guided approach to target identified domain declines may be more effective in preventing frailty progression.